Gender differences in ground reaction forces during running and agility-type motions - Nakamura, B.; Orloff, H.; Warner, M. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Foot and gait characteristics are different between genders. The purpose of this study was to determine if gender has an effect on ground reaction force characteristics during running and agility-type motions. Twenty-two apparently healthy female (73.8±8.4kg; 1.74 ±0.06 m) and seven male (73.5 ±5.3 kg; 1.68 ±0.02 m) current or recently graduated NCAA Division III athletes voluntarily participated in this study. Subjects wore a volleyball shoe while performing four different actions: running, cutting, shuffling, and back cutting. Three 2x4 repeated measures ANOVAs (á<0.05) were used to determine if there were significant differences between gender and the agility-type motions for vertical force, medial/lateral force, and contact time. Significant interaction effects were observed in the vertical (p=0.005), medial/lateral (p=0.046), and contact time (p=0.026).